The essence of money laundering – selected security issues - Jakubiec, Wojciech (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*99.98px); top: calc(var(–scale-factor)*242.91px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.00866);" role="presentation">Combating the crime of money laundering is of key <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*253.23px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.994159);" role="presentation">importance for stabilizing the economy of every democratic state. <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*263.58px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.98329);" role="presentation">Threats posed by the introduction of huge amounts of money from <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*274.02px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.0414);" role="presentation">criminal activities into circulation are extremely <span dir="ltr" style="left: calc(var(–scale-factor)*237.41px); top: calc(var(–scale-factor)*274.02px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.994223);" role="presentation">high and pose a <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*284.34px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.04125);" role="presentation">direct threat to the financial economy of the state, which in fact <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*294.66px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.0063);" role="presentation">leads to its destabilization. The scale of undertakings undertaken <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*304.98px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.08128);" role="presentation">on the international arena confirms the huge profits made by <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*315.42px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.07593);" role="presentation">criminal groups from their illegal activitie<span dir="ltr" style="left: calc(var(–scale-factor)*213.53px); top: calc(var(–scale-factor)*315.42px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.05862);" role="presentation">s. In order to combat <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*325.74px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.962684);" role="presentation">this practice properly, it is necessary to recognize this phenomenon <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*336.06px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.999107);" role="presentation">at an early stage. For this purpose, specialized bodies have been <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*346.38px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.06756);" role="presentation">established whose task is to identify threats related to money <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*356.82px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.11066);" role="presentation">laundering and transfer this informa<span dir="ltr" style="left: calc(var(–scale-factor)*199.49px); top: calc(var(–scale-factor)*356.82px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.0944);" role="presentation">tion to law enforcement <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*367.14px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.04921);" role="presentation">authorities, which will take action to identify the criminal group. <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*377.46px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.07302);" role="presentation">In accordance with international standards, the legislator has <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*387.78px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.0383);" role="presentation">criminalized the phenomenon of money laundering, as only the <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*398.10px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.976455);" role="presentation">involvement of law enforcement agencies <span dir="ltr" style="left: calc(var(–scale-factor)*206.33px); top: calc(var(–scale-factor)*398.10px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.00062);" role="presentation">ensures the proper fight <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*408.54px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.07825);" role="presentation">against this practice. The <span dir="ltr" style="left: calc(var(–scale-factor)*157.73px); top: calc(var(–scale-factor)*408.54px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.10752);" role="presentation">mere penalization of criminal law <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*418.86px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.02322);" role="presentation">provisions is not sufficient. Due to the fact that law enforcement <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*429.18px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.01078);" role="presentation">authorities themselves do not have information about suspicious <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*439.52px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.01145);" role="presentation">transactions that may bear the hallmark<span dir="ltr" style="left: calc(var(–scale-factor)*202.25px); top: calc(var(–scale-factor)*439.52px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.01801);" role="presentation">s of money laundering. It <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*449.96px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.976221);" role="presentation">is reasonable to emphasize the importance of cooperation not only <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*460.28px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.955091);" role="presentation">between <span dir="ltr" style="left: calc(var(–scale-factor)*85.31px); top: calc(var(–scale-factor)*460.28px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.993);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*104.26px); top: calc(var(–scale-factor)*460.28px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.02963);" role="presentation">authorities <span dir="ltr" style="left: calc(var(–scale-factor)*152.59px); top: calc(var(–scale-factor)*460.28px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.10554);" role="presentation">within <span dir="ltr" style="left: calc(var(–scale-factor)*184.14px); top: calc(var(–scale-factor)*460.28px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.002);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*203.20px); top: calc(var(–scale-factor)*460.28px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.932813);" role="presentation">state <span dir="ltr" style="left: calc(var(–scale-factor)*228.15px); top: calc(var(–scale-factor)*460.28px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.07925);" role="presentation">but <span dir="ltr" style="left: calc(var(–scale-factor)*248.18px); top: calc(var(–scale-factor)*460.28px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.922222);" role="presentation">also <span dir="ltr" style="left: calc(var(–scale-factor)*270.13px); top: calc(var(–scale-factor)*460.28px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.995625);" role="presentation">on <span dir="ltr" style="left: calc(var(–scale-factor)*286.68px); top: calc(var(–scale-factor)*460.28px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.993);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*470.60px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.08665);" role="presentation">international arena. The article refers not only to the criminal <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*480.92px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.06272);" role="presentation">policy in the field of money laundering, b<span dir="ltr" style="left: calc(var(–scale-factor)*210.77px); top: calc(var(–scale-factor)*480.92px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.970331);" role="presentation">ut also emphasizes the <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*491.36px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.03438);" role="presentation">role <span dir="ltr" style="left: calc(var(–scale-factor)*67.55px); top: calc(var(–scale-factor)*491.36px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.0325);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*80.86px); top: calc(var(–scale-factor)*491.36px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.998487);" role="presentation">cooperation <span dir="ltr" style="left: calc(var(–scale-factor)*132.17px); top: calc(var(–scale-factor)*491.36px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.955091);" role="presentation">between <span dir="ltr" style="left: calc(var(–scale-factor)*169.48px); top: calc(var(–scale-factor)*491.36px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.993);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*187.23px); top: calc(var(–scale-factor)*491.36px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.02676);" role="presentation">relevant <span dir="ltr" style="left: calc(var(–scale-factor)*224.52px); top: calc(var(–scale-factor)*491.36px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.03253);" role="presentation">institutions, <span dir="ltr" style="left: calc(var(–scale-factor)*275.51px); top: calc(var(–scale-factor)*491.36px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.01487);" role="presentation">which <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*501.68px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.994443);" role="presentation">enables the effective fight against this practice. In connection with <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*512.00px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.00857);" role="presentation">the above, the aim of the article is to analyze the phenomenon of <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*522.32px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.0248);" role="presentation">money laundering from the perspectiv<span dir="ltr" style="left: calc(var(–scale-factor)*196.94px); top: calc(var(–scale-factor)*522.32px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.05354);" role="presentation">e of the criminalization of <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*532.76px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.993864);" role="presentation">provisions <span dir="ltr" style="left: calc(var(–scale-factor)*92.01px); top: calc(var(–scale-factor)*532.76px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.08188);" role="presentation">that <span dir="ltr" style="left: calc(var(–scale-factor)*113.46px); top: calc(var(–scale-factor)*532.76px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.992857);" role="presentation">are <span dir="ltr" style="left: calc(var(–scale-factor)*131.80px); top: calc(var(–scale-factor)*532.76px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.00275);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*149.80px); top: calc(var(–scale-factor)*532.76px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.903429);" role="presentation">basis <span dir="ltr" style="left: calc(var(–scale-factor)*174.73px); top: calc(var(–scale-factor)*532.76px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.12147);" role="presentation">for <span dir="ltr" style="left: calc(var(–scale-factor)*192.00px); top: calc(var(–scale-factor)*532.76px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.00275);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*209.99px); top: calc(var(–scale-factor)*532.76px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.986111);" role="presentation">effective <span dir="ltr" style="left: calc(var(–scale-factor)*247.77px); top: calc(var(–scale-factor)*532.76px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.11056);" role="presentation">fight <span dir="ltr" style="left: calc(var(–scale-factor)*271.76px); top: calc(var(–scale-factor)*532.76px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.0325);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*285.07px); top: calc(var(–scale-factor)*532.76px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.0275);" role="presentation">law <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*543.08px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.956275);" role="presentation">enforcement agencies. <span dir="ltr" style="left: calc(var(–scale-factor)*135.74px); top: calc(var(–scale-factor)*543.08px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.16667);" role="presentation">To <span dir="ltr" style="left: calc(var(–scale-factor)*149.66px); top: calc(var(–scale-factor)*543.08px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.01773);" role="presentation">present the intended goal, methods of <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*553.40px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.98529);" role="presentation">literature research were used with an emphasis on the Pro-<span dir="ltr" style="left: calc(var(–scale-factor)*274.01px); top: calc(var(–scale-factor)*553.40px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.939886);" role="presentation">Quest, <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*563.72px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.918556);" role="presentation">Scopus and Science-<span dir="ltr" style="left: calc(var(–scale-factor)*124.22px); top: calc(var(–scale-factor)*563.72px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.965719);" role="presentation">Direct databases and <span dir="ltr" style="left: calc(var(–scale-factor)*207.05px); top: calc(var(–scale-factor)*563.72px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.03236);" role="presentation">public data.